Templated mesoporous nanomaterials by aerosol route: History and new insights of green chemistry approaches - Lombardo, Maria Veronica (2019)
The combination of aerosol (spray drying process) with sol–gel chemistry has become in, the lasts decades one, of the most promising synthesis routes for the synthesis of industrially scalable mesoporous materials for various applications such as energy, catalysis, water purification, etc. In the spray drying method a precursor solution is atomized to form droplets by ultrasonic nebulization. Each drop can be considered as an individual microreactor. The resulting droplets are then driven by a carrier gas and pass through a hot tube where the solvent is rapidly evaporated and the dissolved precursor species are assembled to generate the products. This method allows the continuous production of a wide variety of materials minimizing the use of precursors and considerably reducing the waste generated during the synthesis. The spray drying method permits to obtain particles with a high-purity in a simple, economical and continuous way. This method allows to produce spherical shaped particles that are agglomeration free and have a relatively monodisperse size, which is very useful for material processing. In this mini-review, we present the basic principles of nanomaterials synthesis using aerosol methods and we discuss the possibility to adapt these processes to the principles of green chemistry.